Sahidic Coptic Leviticus: its manuscript witnesses and its text - St. Demiana, Antonia (Texts and studies in Eastern Christianity, 2025)
"In Sahidic Coptic Leviticus, Antonia St Demiana fully documents, for the first time, the manuscript evidence of Sahidic Leviticus, and offers a codicological investigation and reconstruction of its codices and fragments. An introductory textual study and translation analysis of the text also appears here. Until recently, the Sahidic Old Testament has received little attention. By surveying previous scholarship on the reconstruction of dispersed Sahidic Leviticus fragments and folios, codices formerly considered to be independent of one another are unified, and new Leviticus fragments are identified and virtually assigned to their original codices. This volume also offers new and conclusive observations on the nature of the Sahidic version of Leviticus, and the relationship between the Sahidic and Greek texts of Leviticus"--